Caracterización bioquímica de cianobacterias de la Región Loreto – Perú,2021 - Condori Mamani, Ruth Celestina (2023)
Cyanobacteria have been used throughout history as a dietary supplement, as a matrix for pharmaceutical products, as anticancer agents, and they have also shown great potential in bioremediation. Therefore, the objective of this study was to isolate and biochemically characterize cyanobacteria from the Loreto Region, Peru. Collection was carried out using a 20 µm phytoplankton net, and samples were enriched with BG-11 and CHU N°10 media. Isolations were performed using the pour plate method and serial dilutions. For identification, taxonomic keys were used, and growth profile was evaluated by dry weight. For biochemical tests, lipid content was evaluated following Flores et al. (2020), total proteins by Hartree (1972), and carbohydrates by Dubois et al. (1956). The study succeeded in isolating two species: Synechococcus sp. and Nostoc sp. The growth profile of Nostoc sp. reached a maximum of 4.05 µg and a minimum of 3.75 µg, while Synechococcus sp. showed a maximum of 9.20 µg and a minimum of 8.55 µg. Biochemically, Nostoc sp. exhibited a 3.43% lipid content, 55.19% carbohydrates, and 23.53% proteins. Meanwhile, Synechococcus sp. displayed 16.36% lipids, 17.48% carbohydrates, and 57.56% proteins. In conclusion, the isolated cyanobacteria in this study show optimal values of lipids, carbohydrates, and proteins, suggesting their potential for future applications in food.